Performance Evaluation of FCFS and EBF in Linear and Non-Linear Gridlet Size - Bhardwaj, Neha; Karambir; Jangra, Ajay (International Journal of Computer Sciences and Engineering, 2025)
Grid computing define as the infrastructure in which hardware as well as software resources situated at different places; shared and uses by the different organizations which coordinated to provide consistent, pervasive and transparent access. Workflow is a set of task or subtasks having dependency among them. Resource allocation is one the objective of grid computing. Efficiently use of resources to run the workflow tasks in order to achieve maximum utilization of resources. Throughput is amount of information process in given amount of time. This parameter is mainly applied to various phenomenon’s of networking systems. In this paper, first come first serve and easy backfilling algorithm performance evaluated on the basis of linear and non-linear increase in gridlet size and compare the result in both the cases. The results indicate that EBF has better resource utilization and throughput than FCFS.